Study of Polymeric Membranes Potential for Eugenol Purification from Crude Clove leaf Oil - Tutuk Djoko Kusworo; Danny Soetrisnanto; Widayat Widayat; Budiyono Budiyono; Dani Puji Utomo (Department of Chemical Engineering, Universitas Gadjah Mada, 2019)
Clove oil is an agricultural commodity with economic value. This essential oil can be obtained from flowers, stems, and leaves of clove plants. The quality of clove oil can be evaluated from eugenol levels in oil. An increase in eugenol levels from 70% to 98% can increase oil prices by up to 3 times. Oil obtained from clove leaves has a low eugenol content of 60-70%, therefore the purification is needed to improve the quality of oil. Membrane based separation for eugenol purification was suggested in this paper as new concept in essential oils purification processes. This study aimed to explore the suitable polymer as membrane material for eugenol purification. PES, PA, CA and PI were used in this study, where the membranes were prepared via NIPS technique using manual casting knife to form flat sheet membranes. The membranes were immersed in eugenol to evaluate the solubility. The insoluble membrane was used for purification performance test in membrane filtration cell. The results show that PES and PA membranes were completely dissolved in eugenol in less than 1 minute, while PI and CA membranes were insoluble in eugenol. However, the PI membrane has much lower solvent permeability than CA membrane. The thermal annealed PES membrane for 3 h at 180°C dissolved in eugenol in 30 minutes for complete dissolution. It is concluded that PI and CA membranes can be used as membrane material for eugenol purification but CA more favorable, while PES membrane has a potential for similar purposes after being thermal annealed. However, these findings can offer an important reference for the application of polymeric membranes for clove oil purification through an effective and efficient process.